Efficient use of Spent Activated Coal at Shurtan Gas-Chemical Complex - I., Kamandiyorov B.; N., Musaev M. (European Journal of Life Safety and Stability (2660-9630), 2022)
Effective use of activated carbon used in rolled products production at LLC "Shurtan Gas Chemical Complex", based on the restoration of the adsorption properties of activated carbon or its utilization.